Pharmacokinetics and bioequivalence study of two digoxin formulations after single-dose administration in healthy Chinese male volunteers - Zhang, Xue-Yu; Tian, Yuan; Zhang, Zun-Jian; Rui, Jian-Zhong; Cao, Xiao-Mei (Arzneimittelforschung, 2011)
The pharmacokinetics and relative bio-availability/bioequivalence of two formulations of digoxin (CAS 20830-75-5) were assessed in this paper. The study was conducted in 20 healthy Chinese male volunteers according to an open, randomized, single-blind, 2-way crossover study design with a wash-out phase of 14 days. Blood samples for pharmacokinetic profiling were taken up to 72 h post-dose and digoxin plasma concentrations were determined by a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. Based on the plasma concentration-time data of each individual during two periods, pharmacokinetic parameters, Cmax, AUC0–τ, AUC0–∞ and t1/2, were calculated by applying non-compartmental analysis. Pharmacokinetic data for test and reference formulations were analyzed statistically to evaluate bioequivalence of the two formulations. After oral administration, the values of Cmax, Tmax, t1/2, AUC0–τ, AUC0–∞ for test and reference formulations were 2.61 ± 0.98 and 2.68 ± 1.09 ng/mL, 1.0 ± 0.4 and 1.0 ± 0.4 h, 27.94 ± 3.14 and 27.56 ± 3.86 h, 28.57 ± 4.99 and 28.77 ± 6.53 ng · h/mL, 33.44 ± 4.85 and 33.63 ± 7.57 ng · h/mL, respectively. Both primary target parameters, AUC0–∞ and AUC0–τ, were tested parametrically by analysis of variance (ANOVA). Relative bioavailabilities were 102.5 ± 19.2% for AUC0–∞, 102.0 ± 19.3% for AUC0–τ. Bioequivalence between test and reference formulations was demonstrated for both parameters, AUC0–∞ and AUC0–τ. The 90% confidence intervals of the T/R-ratios of logarithmically transformed data were in the generally accepted range of 80%–125%, which means that the test formulation is bioequivalent to the reference formulation of digoxin.
Keywords: Bioequivalence; Cardiac glycoside; Digoxin; Pharmacokinetics